Strategic source evaluation: addressing the container conundrum. Issue 3 (30th September 2019) - Russo, Alyssa; Jankowski, Amy; Beene, Stephanie; Townsend, Lori
Abstract : Purpose: This paper argues that information containers provide valuable context clues that can help students make choices about how to engage with information content. The authors present a strategic approach to source evaluation rooted in format and authority threshold concepts. Design/methodology/approach: The authors developed a source evaluation strategy with the objective of deciding whether to trust an information source. This strategy involves a set of cues to help readers mindfully engage with both the container and content of a given source. Findings: When conducting research, non-experts are asked to evaluate content in the absence of relevant subject expertise. The cues presented in this paper offer practical tactics informed by the concepts of authority (to help make an accessible judgment of intellectual trust) and format (to help make more informed decisions about the content they find in a browser). Originality/value: While librarians have produced many evaluative models and checklists to help students evaluate information, this paper contributes a unique strategic approach grounded in two information literacy threshold concepts – format and authority – and enacted through a series of actions drawn from website evaluation models, fact-checking, and metacognitive exercises.